PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 002 SINTONG KECAMATAN TANAH PUTIH - Khoirul Anwar; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Problems in research this is be backgrounded to back by its low of result study mathematics IV sd class Country 002 Soil Sintong White with average class 63,50. Drai 20 student that yet to reach KKM many 13 people 65% whereas that had to reach KKM many 7 people 35%, the minimumal completing criteria-value (KKM) mathematics is 70. this Research is Class Action Research (PTK) that have go to to to level it result study mathematics of student IV SD class Country 002 Sintong, with to apply it Mathematics Studying Realistik Indonesia (PMRI). As for formula of the problem is what implement mathematics studying realistik Indonesia (PMRI) can to level it result study mathematics IV SD class Country 002 Sintong. data Collection Instrument to research this is activity sheet and student also studying result. from result activity research in studying process to cycle meeting I first be obtained value average 67,5, and second meeting to level become 77,5%. To cycle meeting II first 82,5% and second meeting to level become 87,5%. the activity data analysiical-Result student to cycle I first meeting 60% and second meeting to level become 67,5%. To cycle meeting II first 75% and second meeting to level become 85%. the To be based of data analysiical-result, average result study before action adalahrata-flat 63,50 finish 7 people (35%). After action level to I's cycle with average 70,25 finish 12 people (60%). To cycle II level with average 82,75 finish 18 people (90%). Mean that mathematics studying implement realistik Indonesia (PMRI) can to level it result study mathematics IV SD class Country 002 Soil Sintong WhiteKey Word : Mathematics Studying Realistik Indonesia (PMRI), Result Study Mathematics